A chapter in the modernization of Turkey: damming the rivers, claiming the natural landscape, and building of the Seyhan Dam in Cilicia. (27th May 2021) - Tozoglu, Ahmet Erdem
ABSTRACT: This article examines building of the Seyhan Dam (1953–1956) in Turkey. Both Turkish and American agents played significant roles for planning and implementation of the project during the Cold War era. The 1950s provided necessary conditions in Turkey for the rise of new actors and developments to facilitate transition from limited modernity, which had mostly manifested in urban areas, to a more comprehensive state of modernity extended to rural areas. This extension had irrevocable impacts on the natural landscape as well. By referring to some patterns of modernization, this article posits building of the Seyhan Dam as a significant example to demonstrate how state-led modernization extended its scope by means of taming rivers and opening of plains for agriculture in the Cilician (Çukurova) region from late Ottoman to Republican periods.